A Mine Valuation Model Incorporating Risk Adjustment And Differential Cost Escalation - R. W. Lake (Society for Mining, Metallurgy & Exploration, 1977)
The decision to develop an ore body can lead to multi-million dollar profits, or equally substantial losses. Accordingly, the effort required to adapt a valuation model to the specific proposal at hand, or even the development of a new model from basic principles, is clearly warranted. In the formulation of a model of this nature, one is faced with some major questions. For example, with the long term obligations that it implies, on what basis should a decision to initiate mining operations be made? Furthermore, how can the vagaries of inflation and the uncertainties that shroud the future be accommodated? Beyond the general principles by which mineral deposits are evaluated, specific cost behaviour is a function of the geology of the deposit, and of the mine design. Moreover, mine design, during the life of the mine, must be a continuing process somewhat akin to dynamic programming. An initial, apparently optimal, design is selected and mining commences. With production, a continual process of information updating leads to revisions. Thus if the maximum value is to be obtained, the mine design must be adjusted to conform to the changed conditions.